2014
DOI: 10.1007/s12013-014-0308-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Farmer’s Lung in Greenhouse Farmers: An Epidemiological Study of 5,880 Farmers from Northeast China

Abstract: The objectives of this epidemiological study were to evaluate the prevalence of farmer's lung disease (FLD) and to explore the potential risk factors for FLD among Chinese greenhouse farmers. A total of 835 plastic film greenhouses, including 5,880 active farmers who engaged in crop cultivation or poultry farming, were randomly selected from the rural regions of Northeastern China. These farmers participated in the study by answering a medical questionnaire. 5,420 greenhouse farmers accepted and answered quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…We found about 11 insecticides are commonly used in greenhouses for insects, nematodes and mites control, with application rates ranged from 1 -2.5 kg/ha ( [34] who reviewed the evidence on the association between working in greenhouses and the occurrence of and respiratory disorders and indicated that greenhouse exposure is associated with an increased risk of respiratory disorders, sensitization to allergens and skin reactions. Further supports to our hypothesis come from the work of Liu et al [33] who evaluated the prevalence of farmer's lung disease (FLD) and revealed that prevalence of FLD among these farmers was 5.7% (308/5420) and the risk factors for FLD were years of age, shorter time interval for re-entry greenhouse, ventilation frequency of greenhouse. In addition, the risk factors emerged from insecticide application can be classified to four cases according to ACHE activity: case 1, extreme risk group included farmers got slight ataxia and having the lowest ACHE activity (538 ± 302), case 2, high risk, included farmers got convulsions tremors and having ACHE activity (1829 ± 1048), case 3, moderate risk, included farmers got dizziness, and headache and having ACHE activity (6000 ± 1414) case 4, Low risk, included farmers got vomiting, and diarrhea, Nozai and having (8389 ± 1622) whereas the normal range of ACHE activity was (14100 ± 2798) included farmers not exposed to pesticides in greenhouse (control sample) more details are shown in Table 2.…”
Section: Risk Factors Emerged From Pesticide Applicationsupporting
confidence: 81%
See 1 more Smart Citation
“…We found about 11 insecticides are commonly used in greenhouses for insects, nematodes and mites control, with application rates ranged from 1 -2.5 kg/ha ( [34] who reviewed the evidence on the association between working in greenhouses and the occurrence of and respiratory disorders and indicated that greenhouse exposure is associated with an increased risk of respiratory disorders, sensitization to allergens and skin reactions. Further supports to our hypothesis come from the work of Liu et al [33] who evaluated the prevalence of farmer's lung disease (FLD) and revealed that prevalence of FLD among these farmers was 5.7% (308/5420) and the risk factors for FLD were years of age, shorter time interval for re-entry greenhouse, ventilation frequency of greenhouse. In addition, the risk factors emerged from insecticide application can be classified to four cases according to ACHE activity: case 1, extreme risk group included farmers got slight ataxia and having the lowest ACHE activity (538 ± 302), case 2, high risk, included farmers got convulsions tremors and having ACHE activity (1829 ± 1048), case 3, moderate risk, included farmers got dizziness, and headache and having ACHE activity (6000 ± 1414) case 4, Low risk, included farmers got vomiting, and diarrhea, Nozai and having (8389 ± 1622) whereas the normal range of ACHE activity was (14100 ± 2798) included farmers not exposed to pesticides in greenhouse (control sample) more details are shown in Table 2.…”
Section: Risk Factors Emerged From Pesticide Applicationsupporting
confidence: 81%
“…Similarly, they found methamidophos-treated groups had significantly lower butyrylcholinesterase and paraoxonase activities. In a different study, Liu et al [33] evaluated the prevalence of farmer's lung disease (FLD) and the potential risk factors for FLD among Chinese greenhouse farmers. They revealed that prevalence of FLD among these farmers was 5.7% (308/5,420) and the risk factors for FLD were years of age, shorter time interval for re-entry greenhouse, ventilation frequency of greenhouse.…”
Section: Introductionmentioning
confidence: 99%
“…In the Southeast United States, the weather tends to be warm and humid. Such climate as well as its proximity to Atlantic Ocean promotes mold growth, a major exposure culprit for cHP [13,14].…”
Section: Morisset Et Al Recently Used a Modified Delphi Survey From mentioning
confidence: 99%
“…Hypersensitivity pneumonitis has recently been associated with greenhouse farming—an agricultural practice that is increasingly common. In an epidemiological survey performed in Northeastern China, it was found that nearly 6% of greenhouse farmers were diagnosed with HP [21], along with nearly a quarter of subjects exhibiting upper respiratory tract infection symptoms, 19% exhibiting bronchial asthma, and 17% with COPD. In this study, risk factors for farmer’s lung included high humidity, large greenhouse size and low greenhouse height, greenhouse ventilation frequency greater than once in 4 hours and less than 30 minutes ventilation durations.…”
Section: Hypersensitivity Pneumonitismentioning
confidence: 99%